Orkes Keroncong (OK) Mutiara Ross di Surabaya (Sejarah, Bentuk Musik, dan Pewarisan) - Senyum Sadhana (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Orkes Keroncong Mutiara Ross is one Keroncong orchestras in Surabaya that involves members across generations, besides that researchers chose object of this study because they saw that inheritance of keroncong is one of important aspects in cultural inheritance and preservation of keroncong music. using a qualitative descriptive approach that focuses on data not numbers, there are 5 characteristics of qualitative research, namely: (1) naturalistic, (2) descriptive data, (3) process (4) inductive (5) meaning. Implications of concept of qualitative methods in this study are; (1) naturalistic, as a direct source of data, in this case researcher goes directly to the data source, (2) descriptive data, that has been collected by researchers in form of interview transcripts, field notes, photography, videotape, personal documents, memos, and recordings official, (3) process, concentration of activities carried out and become the result or product, (4) meaning. increase awareness related to their lives. the focus of this research are; (1) history; OK Mutiara Ross which was founded in 2006 by Mr. Suparman and prioritizes the spirit of all ages. (2) musical form; The form of music used by OK Mutiara Ross is to make keroncong music arrangements with various types of styles. (3) inheritance; OK Mutiara Ross's regeneration occurred because of a familial relationship.